L’accession des femmes à la magistrature non-professionnelle : Un parcours de combattante entre arguments naturalistes et réalité du terrain. Mise en parallèle des cas belge et français - Mathilde van Ackere (Criminocorpus, 2025)
In Belgium, women acquired the right to be lay judges through the Law of May 15, 1910, regarding labor courts, and the Law of June 13, 1924, concerning commercial courts. In France, they acquired this right respectively through the Law of November 15, 1908, and the Law of December 9, 1931. An analysis of the preparatory works for these laws allows for the construction of a typology of the various arguments raised by the proponents of these legislative projects as well as their opponents. The latter notably put forward naturalistic arguments, relying on a supposed feminine nature and inherently feminine professions. Our study highlights the fact that these arguments come into conflict with on-the-ground realities, as emphasized by proponents of the reforms: the significant number of female workers, employees, and business owners; the presence of women leading major businesses; and the increasing access of women to a growing range of professions and positions.